KOMPETENSI MANAJEMEN DOKTER DI FASILITAS PELAYANAN KESEHATAN PADA DAERAH TERTINGGAL DI INDONESIA: KEBUTUHAN DAN TANGGUNG JAWAB INSTITUSI PENDIDIKAN KEDOKTERAN - Fury Maulina; Riris Andono Ahmad; Mubasysyir Hasanbasri (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: challenges to work in underdeveloped areas and people’s expectations of the quality of healthcare requires doctors who have public health program management competencies. Objectives: identify perception of the needs and responsibility of medical education institution to meet the management competencies. Method: a mixed method study mixed method with sequential exploratory. Results: Communication skills and respecting the right of others are the most needed competencies and the less needed competency is become chairman/leader of an activity. Competency to manage the organization’s finances have not been met by a medical education institution and competency which has been met by medical education institutions is an updating of medical knowledge actively. Conclusion: doctors need management competencies while on duty in underdeveloped areas, but medical education institutions are not yet fully meet its responsibilities in the fulfilment of these competencies.